Analysis of the Influence of CSR Categories on Company Value in Consumer Goods Companies Listed on Indonesia Stock Exchange - Dara, Rifdah Riyan; Siregar, Hasrul; Faridani, Mutia Riska; Pardede, Sovia Lolita Apriani; Wongsosudono, Corinna (Journal of Business Management and Economic Development, 2026)
This study aims to analyze the effect of corporate social responsibility disclosure and financial performance on company value in consumer goods companies listed on the Indonesia Stock Exchange from 2021 to 2023. This study uses a descriptive quantitative method with a sample of 32 companies from a total population of 96 companies. The data was processed using classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results of this study indicate that, partially, CSR does not have a significant effect on company value, while financial performance has a significant effect. However, simultaneously, both are proven to have a significant effect on company value, with a contribution of 22.5% to the variation in company value, while the remaining 77.5% is influenced by other factors outside the scope of this study.